Addition of Purified Tannin Sources and Polyethylene Glycol Treatment on Methane Emission and Rumen Fermentation in Vitro - Anuraga Jayanegara; H.P.S. Makkar; K. Becker (Faculty of Animal Science, Bogor Agricultural University, 2015)
The objectives of this experiment were (1) to observe the effects of purified tannins and polyethy-lene glycol (PEG) on in vitro rumen fermentation and methanogenesis, and (2) to assess the accuracy of volatile fatty acid (VFA) profiles in predicting methane emission. Hydrolysable and condensed tannins were extracted and purified from chestnut, sumach, mimosa and quebracho. Hay and concentrate mixture (70:30 w/w, 380 mg) was incubated in Hohenheim glass syringe containing 10 mL rumen liquor + 20 mL buffer. The purified tannins were injected into the syringes at a concentration of 1.0 mg/mL each, either without or with PEG 6,000 addition in three replicates. Results revealed that a decrease of methane emission (20%-27%) was observed when the purified tannins were added into basal diet as compared to control (P<0.05), and PEG addition increased methane emission (P<0.05). All purified tannins decreased total gas and total VFA production (P<0.05). The H2 recovery of the treatments ranged from 86.7% to 95.3%. Estimation of methane emission by using VFA profiles revealed an accurate result with a very low root mean square prediction error (1.75%). It is concluded that tannins mitigate methane emission while PEG neutralize such effect, and VFA profiles are accurate predictors of the emission.Key words: tannin, polyethylene glycol, methane, rumen, stoichiometry